Students’ Perceptions Of Using Dictation In English Classes: A Study On Eighth Graders - Syarifah Widya Ulfa; T. Khoirunnisa.YL; Miftahul Jannah; Siti Sholikhah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to explore the perceptions of eighth grade students towards the use of dictation method in English language learning. This study used qualitative methods, through questionnaires and in-depth interviews. The results showed that the majority of students viewed dictation as an effective tool to improve their listening and writing skills. Students felt that dictation helped improve spelling and expand vocabulary. However, some students found dictation boring and challenging, especially for those with hearing disabilities. The study concluded that although dictation has its own challenges, its benefits in supporting English language learning are significant. Recommendations for teachers include diversifying teaching methods to maintain student interest and providing additional listening practice for students who need it.